Study on the characteristics and mechanism of bacteriophage MS2 inactivated by bacterial cellulose supported nanoscale zero-valent iron. (10th October 2020) - Yuan, Donghai; Zhai, Linxiao; Zhang, Xueyao; Cui, Yanqi; Wang, Xinyi; Zhao, Yinxiu; Xu, Hongdeng; He, Liansheng; Yan, Chenling; Cheng, Rong; Kou, Yingying; Li, Junqi
Abstract: The nano zero valent iron (nZVI) is an efficient environmental remediation material, but it is easy to be oxidized and agglomerated, which limits its application in the environment. In this paper, bacterial cellulose membrane was used as a carrier material to reduce three different concentrations of ferrous ions by in-situ liquid-phase reduction method using sodium borohydride, and three kinds of bacterial cellulose membrane loaded with nanometer zero valent iron (BC-nZVI) samples were successfully prepared. The physical and chemical properties of BC-nZVI before and after the reaction were characterized by SEM, XRD and XPS. The effects of pH, dose and reactive oxygen species (ROS) on the inactivation of bacteriophage MS2 were studied. The results showed that nano-zerovalent iron was successfully loaded on the bacterial cellulose membrane. The particle size of nZVI particles loaded in BC-nZVI was about 200 nm under the condition of low ferrous sulfate, effectively alleviating the agglomeration phenomenon. And the inactivation efficiency of BC-nZVI on MS2 has been improved, reaching 4 log in 5 min. BC-nZVI showed two stages of inactivation characteristics, the first stage was 5 min to achieve 4 log high-efficiency inactivation stage, the second stage was the follow-up slow inactivation stage. At different pH value, the removal rate of MS2 by BC-nZVI increased with the increase of pH value, which was different from that of nZVI. The radical scavenger experiments showed that the main factor affecting the removal rate of MS2 in the first stage was O2 −, followed by Fe (IV), while the effect of OH was not significant. In the second stage, the main influencing factors was OH. Under alkaline condition, the yield of O2 − was increased, the reaction time was prolonged, and the deactivation rate of MS2 was increased. These results provide new ideas for the practical application of nZVI in the treatment of pathogenic microorganisms. Graphical abstract: We synthesize a bacterial cellulose supported nanoscale zero-valent iron (BC-nZVI). The three-dimensional network structure and nanoscale fibers of bacterial cellulose membranes can be used as templates for composite inorganic nanomaterials, and can protect and restrict the formation of nanoparticles in space, preventing the formation of nanoparticles via agglomeration to a certain extent, and avoiding the problems of inorganic nanomaterials, which are difficult to retain as well as to recycle. The material can effectively improve the inactivation efficiency of MS2, and the removal efficiency of MS2 can reach 4 log after 5 min of reaction. Image 1 Highlights: BC-nZVI was successfully synthesized to inactivate bacteriophage MS2. BC NZVI can effectively inactivate MS2 in a short time. BC NZVI can effectively inactivate MS2 at pH 5–9. O2 −, Fe (IV) and OH radicals play a major role in the process of inactivation.